ISLAM, WESTERNIZATION AND THE ROOTS OF MODERNISM IN MUSLIM LAND - Abubakar Muhammad Kolo; Tambari Abbas Bashar (Al-Risalah : Jurnal Studi Agama dan Pemikiran Islam, 2024)
This paper Islam, westernization and the roots of modernism in Muslim land is aim at providing the need insight and the causes of the negative effects of the western modernism among Muslims. The paper discussed the western and Islamic modernization and how both of the civilization contributed to the progress of humanity and how the western modernization has negatively affected the Muslim Ummah around the world. It was discovered that Muslim elites has contributed to the infiltration of the western world into Muslim land either due their quest for power in their various countries. It is also revealed that imitators of the western life styles by Muslims most especially those who have traveled to study in either Europe and America only returned to imitate and spread such tendencies in their societies. It was discovered that Islam follows the wind of change once it is not against the true teachings of Islam and moral values as of Islam. The researchers employed desk review method as a mode of data and information for this research where major literary work was utilised. The paper concluded that, Islam accepted any change that comes it way in as far as it does not go social, economic, political and moral system of Islam as taught in the Qur’an and Sunnah of the Prophet (may peace and blessings of Allah be upon him).